EMBR-28. CNS DISTRIBUTIONAL KINETICS OF PANOBINOSTAT IN THE MOUSE. (1st June 2021) - Zhang, Wenqiu; Mohammad, Afroz; Sirianni, Rachael; Elmquist, William
Abstract: Medulloblastoma (MB) is the most common malignant pediatric brain tumor and has the potential for leptomeningeal spread, often responsible for the preponderance of morbidity and mortality in MB patients. Adverse sequelae following high dose craniospinal radiation and aggressive chemotherapies, including neurocognitive deficits and endocrine disorders, impairs patient quality of life and thus call for new therapeutic strategies. Panobinostat is a pan-histone deacetylase (HDAC) inhibitor that has been shown to be effective against MBs in vitro . The objective of the current study is to evaluate the key pharmacokinetic (PK) parameters and the mechanisms influencing the brain penetration of panobinostat in the mouse model, often used in MB preclinical efficacy trials. Pharmacokinetic studies were conducted using FVB wild-type (WT) mice and triple-knockout (TKO, Mdr1a/b –/– Bcrp1 –/– ) transporter-deficient mice. Panobinostat was administered intravenously (10 mg/kg) and concentrations at selected time points in plasma, brain and spinal cord were determined using LC-MS/MS. PK parameters, including systemic clearances, volumes of distribution, half-lives, and areas-under-the-concentration time curve (AUC) were calculated by using non-compartmental analysis. In WT mice, the CNS penetration was initially limited; however, it increased with time and the brain-to-plasma (B/P) and spinal cord-to-plasma (SC/P) distributional partition coefficients (AUC ratios) were 3.7 and 1.4, respectively. The B/P and SC/P ratios of panobinostat in BBB transporter-deficient TKO mice were 1.7- and 2.3-fold higher than those in WT mice, respectively. Our data suggest that P-glycoprotein (P-gp) and/or breast cancer resistance protein (Bcrp) efflux transporters, localized in BBB, may influence the delivery of panobinostat to tumors in the brain following systemic intravenous administration. These systemic and CNS distributional parameters will inform future preclinical efficacy studies of panobinostat for MB. As such, studies investigating other administration routes that can bypass the BBB, such as the intrathecal injection of novel formulations, are ongoing.